2004
DOI: 10.1016/j.seizure.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and erectile dysfunction: a review

Abstract: The association between epilepsy and erectile dysfunction (ED) has often been described but not clearly defined. This is a review of the literature regarding the current theories on the causes of ED in epilepsy, as well as the evaluation and treatment options available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 72 publications
(100 reference statements)
1
27
0
Order By: Relevance
“…For this reason the choice of the AED should take into account the possible effects on sexuality [82,83]. In patients with epilepsy, percentages of sexual dysfunction is 11-22% during treatment with PB, CBZ, PHT, primidone (PRM).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason the choice of the AED should take into account the possible effects on sexuality [82,83]. In patients with epilepsy, percentages of sexual dysfunction is 11-22% during treatment with PB, CBZ, PHT, primidone (PRM).…”
Section: Introductionmentioning
confidence: 99%
“…In male epileptic patients, decreased libido and potency, loss of sexual desire and erectile dysfunctions have been noted frequently. While 3–9% of healthy men have erectile dysfunctions, 57% of male epilepsy patients experience this (Smaldone et al 2004). Sexual dysfunctions in people with epilepsy might be caused by many factors, of which the three main ones are noted: epilepsy itself, antiepileptic drugs (AEDs) and psychiatric/psychotic problems (Smaldone et al 2004; Stimmel and Gutierrez 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While 3–9% of healthy men have erectile dysfunctions, 57% of male epilepsy patients experience this (Smaldone et al 2004). Sexual dysfunctions in people with epilepsy might be caused by many factors, of which the three main ones are noted: epilepsy itself, antiepileptic drugs (AEDs) and psychiatric/psychotic problems (Smaldone et al 2004; Stimmel and Gutierrez 2006). It was reported that epileptic discharges in the brain might be transmitted through amygdala–hypothalamic pathways, resulting in changes in the release of sexual steroid hormones and in reduced serum concentration of gonadotropins and bioactive testosterone (Herzog 1999; Montouris and Morris 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, methods such as the intercavernosal injection of vasodilators, i.e. papaverine or a grouping of papaverine, phentolamine, and prostaglandin E1, or yohimbine can be used to treat ED (Smaldone et al 2004; Rokkas 2015). Other pharmaco-therapies for combatting ED to enhance the quality and frequency of erection include; topical nitroglycerine, topical minoxidil, and sildenafil (Rokkas 2015).…”
Section: Treatment Of Sexual Dysfunctionmentioning
confidence: 99%